Report of the Working Group on Storage - Planning Commission (Planning Commission, 1968)
A broad review of storage facilities for foodgrains and other agricultural commodities made in the Planning Commission in May 1968 in consultation with representatives of the Central Departments of Food, Agriculture and Cooperation, the Food Corporation of India, the National Cooperative Development Corporation, the Central Warehousing Corporation and the Agricultural Credit Department of the Reserve Bank of India, revealed that available storage capacity with different agencies would, be subject to severe strains in handling the quantities of foodgrains expected to be procured, imported and held in reserve by the end of 1968.
India (Planning Commission)
Planning Commission